2007
DOI: 10.1007/s10327-007-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Glomus intraradices, Pseudomonas alcaligenes, and Bacillus pumilus: effective agents for the control of root-rot disease complex of chickpea (Cicer arietinum L.)

Abstract: The effects of Glomus intraradices, Pseudomonas alcaligenes and Bacillus pumilus on the root-rot disease complex caused by the root-knot nematode Meloidogyne incognita and the root-rot fungus Macrophomina phaseolina in chickpea was assessed by quantifying differences in the shoot dry mass, pod number, nodulation, and shoot content of chlorophyll, nitrogen, phosphorus and potassium. Inoculation of plants with G. intraradices, P. alcaligenes and B. pumilus alone and in combination significantly increased shoot d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Significant differences between different treatments were not observed for shoot P uptake but were higher in all the treatments in comparison with control plants. The present study is in accordance with the other findings that application of consortium of AM fungi, Pseudomonas resulted in increased phosphorus and nitrogen content (Akhtar & Siddique 2008b). Prominent increase in the root N content in consortium of all the bioinoculants indicates that AM fungi might have played little role in the solubilisation of soil minerals, especially phosphorus and nitrogen.…”
Section: Discussionsupporting
confidence: 93%
“…Significant differences between different treatments were not observed for shoot P uptake but were higher in all the treatments in comparison with control plants. The present study is in accordance with the other findings that application of consortium of AM fungi, Pseudomonas resulted in increased phosphorus and nitrogen content (Akhtar & Siddique 2008b). Prominent increase in the root N content in consortium of all the bioinoculants indicates that AM fungi might have played little role in the solubilisation of soil minerals, especially phosphorus and nitrogen.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the intensity of the chickpea root-rot disease complex was reduced after the combined application of Glomus intraradices with either Pseudomonas straita or Rhizobium than when they were applied separately (Akhtar and Siddiqui 2008a). Similarly, the greatest reduction in the chickpea root-rot disease complex was observed when Pseudomonas alcaligenes, Bacillus pumilus and Glomus intraradices were used together (Akhtar and Siddiqui 2008b). Application of Paecilomyces lilacinus with composted cow manure on tomato also gave better control of M. incognita than either did individually (Siddiqui and Akhtar 2008).…”
Section: Introductionmentioning
confidence: 94%
“…PGPR were grown in nutrient broth medium for 72 h at 37°C before their use as biocontrol agents; hence, no significant nutrients remained in the medium (Siddiqui and Akhtar 2008). Similarly, the AM fungal inoculum included a few Rhodes grass segments and some soil particles, but these additions did not significantly affect plant growth (Akhtar and Siddiqui 2008b).…”
Section: Selection Of Biocontrol Agents and Inoculum Preparationmentioning
confidence: 99%
“…According to Moghaddam et al (2014), B. pumilus ToIrFT-KC806241 and ToIrMA-KC806242 showed potential antagonism against M. javanica by reducing the number of galls and eggs in tomato plants. Similarly, B. pumilus reduced the gall formation and reproduction of the root-knot nematode (Akhtar and Siddiqui, 2008). Several studies have reported the nematicidal effect of B. pumilus on root-knot nematodes in different agricultural crops (Pinho et al, 2009;Mekete et al, 2009: Oliveira et al, 2007.…”
Section: Introductionmentioning
confidence: 96%